Penyuluhan dan Dialog Hukum kepada Masyarakat dalam Siaran Radio Live tentang Perusahaan dan Hubungan Ketenagakerjaan - Rolib Sitorus; Joy Zaman Felix Saragih (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
People who work as wage earners from employers often face problems in employment relations due to differences in interpretation and implementation of employment agreements between employers and workers. The implementation of community service activities with the theme of companies and employment relations aims to provide education to workers regarding employment relations and the rights and obligations of workers on the one hand and employers on the other, and aims to ensure that workers know how to resolve employment disputes. The method used and implementing this community service activity is through counseling to the community (workers) using radio media with a 2 (two) way model, namely a resource person on the radio with listeners in another position, and the activity is carried out interactively directly. While the results obtained from this activity are the understanding of the community, especially workers, regarding the rights and obligations of workers on the one hand and the rights and obligations of employers on the other, as well as the steps and procedures for resolving employment disputes. In addition, the community also understands the role of the government and supervises employment relations.